Different sources of reduced carbon contribute to form three classes of terpenoid emitted by Quercus ilex L leaves (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE UNITED STATES OF AMERICA, 1996)
Quercus ilex L. leaves emit terpenes but do not have specialized structures for terpene storage. We exploited this unique feature to investigate terpene biosynthesis in intact leaves of Q. ilex. Light induction allowed us to distinguish three classes of terpenes: (i) a rapidly induced class including alpha-pinene; (ii) a more slowly induced class, including cis-beta-ocimene; and (iii) the most slowly induced class, including 3-methyl-3-buten-1-ol. Using C-13, we found that alpha-pinene and cis-beta-ocimene were labeled quickly and almost completely while there was a delay before label appeared in linalool and 3-methyl-3-buten-1-ol. The acetyl group of 3-methyl-3-buten-1-yl acetate was labeled quickly but label was limited to 20% of the moiety. It is suggested that the ocimene class of monoterpenes is made from one or more terpenes of the alpha-pinene class and that both classes are made entirely from reduced carbon pools inside the chloroplasts. Linalool and 3-methyl-3-buten-1-ol are made from a different pool of reduced carbon, possibly in nonphotosynthetic plastids. The acetyl group of the 3-methyl-3-buten-1-yl acetate is derived mostly from carbon that does not participate in photosynthetic reactions. Low humidity and prolonged exposure to light favored ocimenes emission and induced linalool emission. This may indicate conversion between terpene classes.
APS